1999
DOI: 10.1007/s004180050335
|View full text |Cite
|
Sign up to set email alerts
|

Membrane structure of caveolae and isolated caveolin-rich vesicles

Abstract: Caveolae are specialized invaginated domains of the plasma membrane. Using freeze-fracture electron microscopy, the shape of caveolae and the distribution of intramembrane particles (integral membrane proteins) were analyzed. The caveolar membrane is highly curved and forms flask-like invaginations with a diameter of 80-120 nm with an open porus of 30-50 nm in diameter. The fracture faces of caveolar membranes are nearly free of intramembrane particles. Protein particles in a circular arrangement surrounding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 49 publications
7
26
0
Order By: Relevance
“…As in our previous Western blotting experiments (34), we see no mass spectrometrybased evidence for the caveolae localization of adipocyte proteins involved in insulin's actions, namely the insulin receptor and one of its downstream targets, Glut4. Indeed, the protein composition of adipocyte caveolae obtained rapidly and in reasonable yield is quite simple and in agreement with a previous freeze-fracture study of cultured adipocytes that concluded that there were relatively few proteins in them (42). However, we cannot rule out the possibility that some caveolae-localized proteins escaped our scrutiny and/or that the caveolae population is heterogeneous, as has been suggested (43).…”
Section: Caveolae Isolation Protocols and Problemssupporting
confidence: 89%
“…As in our previous Western blotting experiments (34), we see no mass spectrometrybased evidence for the caveolae localization of adipocyte proteins involved in insulin's actions, namely the insulin receptor and one of its downstream targets, Glut4. Indeed, the protein composition of adipocyte caveolae obtained rapidly and in reasonable yield is quite simple and in agreement with a previous freeze-fracture study of cultured adipocytes that concluded that there were relatively few proteins in them (42). However, we cannot rule out the possibility that some caveolae-localized proteins escaped our scrutiny and/or that the caveolae population is heterogeneous, as has been suggested (43).…”
Section: Caveolae Isolation Protocols and Problemssupporting
confidence: 89%
“…We find caveolae purified by this method to be devoid of GLUT4, the insulin receptor, and flotillin. Indeed, and in agreement with previous freeze fracture studies (28), adipocyte caveolae have a relatively limited protein composition. In addition to the caveolins only two major protein components of caveolae were identified: (a) the semicarbazide-sensitive amine oxidase (SSAO), a very abundant adipocyte protein (29) of unknown physiological significance (30); and (b) the scavenger receptor CD36, which plays an important role in mammalian fatty acid/lipid metabolism (31,32).…”
supporting
confidence: 90%
“…4). The range of vesicle diameter, 30 -130 nm, is broader than observed for native caveolae (70 -80 nm) but corresponds well to that observed for isolated caveolae obtained by coating with cationized silica and/or Triton X-100 extraction (25,26,28).…”
Section: Characterization Of Anti-caveolin Antibody 7c8 -supporting
confidence: 79%
See 1 more Smart Citation
“…Caveolins (at least caveolin-1 and caveolin-3) are necessary for the formation of caveolae (as derived from experiments with knockout mice) (122,123). These and other evidence (124,125) suggest that caveolin-1 is an essential component of caveolae, even if its presence on the cytoplasmic face of caveolae was somehow challenged by theˆnding that caveolin-1 is rather present in intramembrane particles interacting with caveolae surface (126). Caveolin-1 is also found at many other intracellular locations, including the trans-Golgi network and in other organelles (127,128), and caveolin-1 antibodies also bind to ‰at membrane portions (129,130).…”
Section: F Lipid Rafts Markersmentioning
confidence: 96%